Characteristics of frozen-thawed semen of different cattle breeds, storage time, packaging and source of production - Mohd Dzin, Nor Liyana (2016)
The aim of this study is to compare the general and progressive motility, viability, and abnormality characteristics of frozen-thawed semen of different cattle breeds, duration of storage, packaging, and source of production. Sixty six semen samples from eleven breeds packed either in glass ampules or straws that were produced locally or were imported between 1975 and 2010 were evaluated for the above characteristics. Results showed that general motility was significantly different in the different storage duration, breeds and packaging, but not significantly different in the source of production. Progressive motility of thawed sperm was also significantly different in different storage duration, breeds, packaging, and source of production. Viability and abnormality of thawed sperm were significantly different in different storage duration, breeds, and source of production but not significantly different in packaging. Based on the results, it can be concluded that Holstein frozen-thawed semen was the best quality among other breeds. Frozen-thawed semen produced in 1999 was the best quality among the other years. Between packaging, straws have higher general motility compared to glass ampules.While, glass ampules have higher progressive motility compared to straws. Locally produced frozen-thawed semen was examined to be better compared with imported semen.